Rapamycin Antifungal Action Is Mediated via Conserved Complexes with FKBP12 and TOR Kinase Homologs in Cryptococcus neoformans - Cruz, M. Cristina (American Society for Microbiology, 1999)
Cryptococcus neoformans is a fungal pathogen that causes meningitis in patients immunocompromised by AIDS, chemotherapy, organ transplantation, or high-dose steroids. Current antifungal drug therapies are limited and suffer from toxic side effects and drug resistance. Here, we defined the targets and mechanisms of antifungal action of the immunosuppressant rapamycin in C. neoformans. In the yeast Saccharomyces cerevisiae and in T cells, rapamycin forms complexes with the FKBP12 prolyl isomerase that block cell cycle progression by inhibiting the TOR kinases. We identified the gene encoding a C. neoformans TOR1 homolog. Using a novel two-hybrid screen for rapamycin-dependent TOR-binding proteins, we identified the C. neoformans FKBP12 homolog, encoded by the FRR1 gene. Disruption of the FKBP12 gene conferred rapamycin and FK506 resistance but had no effect on growth, differentiation, or virulence of C. neoformans. Two spontaneous mutations that confer rapamycin resistance alter conserved residues on TOR1 or FKBP12 that are required for FKBP12-rapamycin-TOR1 interactions or FKBP12 stability. Two other spontaneous mutations result from insertion of novel DNA sequences into the FKBP12 gene. Our observations reveal that the antifungal activities of rapamycin and FK506 are mediated via FKBP12 and TOR homologs and that a high proportion of spontaneous mutants in C. neoformans result from insertion of novel DNA sequences, and they suggest that nonimmunosuppressive rapamycin analogs have potential as antifungal agents.